PENGARUH PROMOSI DAN PERSEPSI NILAI TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN CICIL.CO.ID DI KOTA SEMARANG) - Arief Darmawan; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2020)
Cicil.co.id is a fintech company, which is innovation services in technology-based finance by targeting prospective student consumers. Cicil.co.id has been present in the city of Semarang since 2018. The number of users in 2019 compared to the number of active students in tertiary institutions in the city of Semarang is still small. This is a problem because the prospective customers of Cicil.co.id are students themselves and what happens in the field is a decrease in certain months in 2019. The study aims to determine the influence of promotion and perception value of the decision of purchase Cicil.co.id through interest in buying as intervening variable. The research is explanatory and the sample collection using a nonprobability technique sampling. Data collection uses a questionnaire from a google form. The sample is 100 respondents of users Cicil.co.id within the city of Semarang. This research using analysis quantitative with validity, reliability, categorisation, a correlation coefficient, the coefficients determination, regression simple and multiple, tabulation cross, significance test t, f test, and sobel test. The result showed the dependent variable of the Purchase Decision (Y)was influenced by two independent variables, namely Promotion (X1) and Perceived Value (X2) and can be mediated by moderating variables namely buying interest. The moderator variable strengthens the relationship between the dependent and independent variables based on the results of the Sobel test calculation. The results of the sobel test Promotion is Z count (3.851)> t table (1.945) with a significance level of 0.000 and the results of the sobel test calculation Perception Value is Z count value (3.999)> t table (3.999) 1,945) with a significance level of 0,000.